Overview of Islamic Law on “Leasing” Implementationin The Indonesian Civil Code - Hasyim, A. Dardiri (UIN Sunan Kalijaga, 2016)
Leasing agreement is a mixture of agreements on purchasing, selling, and renting. In leasing, when a buyer can’t buy goods in cash, then the agreement is held in which the buyer is allowed to repay with several installments. The goods will be owned by the buyer by the time the installments have been paid. Duringthe payment of installments, as long as it is not paid completely, the buyer is still a tenant. As a tenant, the buyer is only allowed to take advantage of the goods and does not have the right to transfer the goods to another person. If the transfer term is broken before the payment of installments is completed, then the buyer will be subjectedto criminal accusations because he/she makes the others’ property lost. Then, the leasing agreement here is likely to lead to a form of a purchase agreement rather than of a renting, for the main point is all about the transfer of property rights. The different status over the ownership of goods will also have different legal consequences. In terms of purchase, a buyer becomes the owner of the goods, which makes him feel free to do over the things possessed, such as leasing them as rental, mortgage, and so on to another party. In terms of leasing, whereas the buyer has not become the owner of the goods, he could not act lawfully over them. While Islam has the basic law upon leasing agreement, it is necessary to implement this law in leasingagreement towards the Indonesia Civil Code.